2022
DOI: 10.1136/svn-2021-001102
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers and cerebral small vessel disease: a community-based cohort study

Abstract: Background and purposeAlthough inflammation has been proposed to be a candidate risk factor for cerebral small vessel disease (CSVD), previous findings remain largely inconclusive and vary according to disease status and study designs. The present study aimed to investigate possible associations between inflammatory biomarkers and MRI markers of CSVD.MethodsA group of 15 serum inflammatory biomarkers representing a variety of those putatively involved in the inflammatory cascade was grouped and assessed in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 41 publications
0
38
1
Order By: Relevance
“… 30 A recently published community-based study with 960 Chinese stroke-free participants observed a significant association between elevated levels of endothelial-related inflammatory biomarkers including YKL-40 and increased WMH volume. 9 In another study with 42 sporadic CSVD patients, CSF levels of YKL-40 were positively correlated with the WMH load. 31 The results of our study suggested that serum YKL-40 levels at baseline, in AIS patients remained significantly associated with PV-WMH after adjusting for potential confounding risk factors, which has never been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“… 30 A recently published community-based study with 960 Chinese stroke-free participants observed a significant association between elevated levels of endothelial-related inflammatory biomarkers including YKL-40 and increased WMH volume. 9 In another study with 42 sporadic CSVD patients, CSF levels of YKL-40 were positively correlated with the WMH load. 31 The results of our study suggested that serum YKL-40 levels at baseline, in AIS patients remained significantly associated with PV-WMH after adjusting for potential confounding risk factors, which has never been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 94%
“… 26 , 27 In recent years, increasing evidence indicates an extraordinarily critical role of inflammation in the progression of WMH. 9 , 24 , 28 , 29 As a glycoprotein mediating inflammation, YKL-40 has been reported to correlated with pulmonary diseases, diabetes mellitus, coronary heart disease, Alzheimer’s disease and stroke. 10 , 11 , 14 However, evidence for the correlation between YKL-40 and CSVD is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current investigation found that higher SAA levels were independently associated with total WMH, implying that dysregulated SAA may play a role in the etiology of overall WMH. However, the bulk of prior investigations has focused on the association of other plasma inflammatory markers [including, total homocysteine (tHcy), hypersensitive-C reactive protein (hs-CRP), vascular cell adhesion molecule-1 (VCAM-1), E-selection, and P-selection] with total WMH burden [26][27][28]. Few researchers have focused on the impact of different variables on PVWHM and DWMH.…”
Section: Discussionmentioning
confidence: 99%
“…Typical neuroimaging features of CSVD on magnetic resonance imaging (MRI) include white matter hyperintensity (WMH), lacunes, enlarged perivascular spaces (EPVS), cerebral microbleeds (CMBs), and brain atrophy (BA) 3 . Previous studies have identified a spectrum of traditional vascular risk factors and blood‐based biomarkers for CSVD 4–7 . However, despite abundant literature on this subject, these is insufficient explanation regarding the biological processes of CSVD.…”
Section: Introductionmentioning
confidence: 99%